Pentagon's Fraud Theory on Student Academic Fraud Behavior: A Study of Accounting Students in State University in Malang City - Anggraini, Rosalina Yuri; Subroto, Bambang; Andayani, Wuryan (The International Journal of Accounting and Business Society, 2024)
Purpose — This study aims to predict the factors that influence the academic fraud behavior of accounting students, especially during online learning. Using the Fraud Pentagon Theory model and Theory of Reasoned Action. Design/methodology/approach — This research develops the Fraud Pentagon Theory and Theory of Reasoned Action models. Data collection used a questionnaire survey with a sample of accounting students at state universities in Indonesia. Sampling technique with convenience sampling Findings — The study results prove that the Fraud Pentagon Theory and Theory of Reasoned Action can predict student academic fraud behavior. Attitude, pressure, and arrogance influenced accounting students' behavioral interest and behavior to commit academic fraud during online learning. In addition, behavioral interest also influences the academic fraud behavior of accounting students when learning online. Behavioral interest partially mediates the influence between attitude, pressure, and arrogance on academic cheating behavior. Practical implications—The Prevention of student academic fraud behavior can be considered from the attitude, pressure, arrogance, and student interest in doing so. The right methods and policies can be applied to increase efforts to suppress academic fraudulent behavior practices by students and build a culture of positive thinking among them. Originality/value — This study presents cases of student fraudulent behavior during online learning methods. The results of this study provide empirical evidence that the collaboration between fraud theory and psychological theory, namely the Fraud Pentagon Theory and Theory of Reasoned Action, can predict student academic fraud behavior. Other fraud behavior research is usually carried out separately between the two theories. Keywords — Attitude, Pressure, Arrogance, Intention, Academic Fraud Behavior, Fraud Pentagon Theory, Theory Reasoned Action. Paper type — Survey Study